'I want my closet back': queering and unqueering language in Giannina Braschi's Yo-Yo Boing!. Issue 2 (1st February 2020) - Jones, Ellen
ABSTRACT: This essay examines how anxieties about language, gender fluidity, and queer desire intersect in Giannina Braschi's 1998 bilingual novel Yo-Yo Boing! . Identifying the novel's 'translingualism' (the ways in which its English and Spanish interact, transform, and enhance one another), as a key part of its textual difficulty, it argues that Braschi's use of language constitutes a queer practice. That language is altered, however, in Tess O'Dwyer's 2011 'translation' of the novel into only English, which this essay reads as an integral part of Braschi's highly self-referential postmodern play. Responding to its own characters' anxieties, it 'un-queers' their language and thus mitigates the novel's difficulty; this complements the strategy of its new publisher, AmazonCrossing, which hopes to appeal to a wide readership. Viewed as a complex, contradictory, collaborative whole, the two versions of Yo-Yo Boing! blur the lines between production and reception, interpretation and praxis, subverting the traditionally hierarchical relationship between original and translation to instead propose the latter as a condition of textual production.